Implementasi Sistem Jaminan Kesehatan Masyarakat (Jamkesmas) terhadap Pelayanan Kesehatan dan Perlindungan Hukum Bagi Masyarakat Peserta Jamkesmas (Puskesmas Kepil II Wonosobo). - ROEMANSYAH, DEDDY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The aim of this research is to know about the Implementation of public Health Insurance system towards health services and legal protection for jamkesmas’ members in Puskesmas Kepil II Wonosobo. Descriptive qualitative with empiric juridical approach is used in analyzing this research. The reason why the researcher uses this qualitative method is to analyze the implementation of the program and identify the obstructions in realizing the program of public insurance system. The result of this research shows that there are inaccuracies data about destitute society who have the right to get the public health insurance. Obscurity of health services and health fund from the government, the differentiate of health services of each Jamskesmas’ members, and also misunderstanding about the process of Jamkesmas administrations. The researcher concludes that to support the implementation of public health insurance, the government of Wonosobo produces some decrees legal protection to protect Jamkesmas’s members like the decree of the head of health department and Social Prosperity of Wonosobo number 440/643/VII/2008 about re-allocation of fund and the numbers of destitute society in each Puskesmas and the fund operational guidance of public health insurance in all of Puskesmas of Wonosobo in 2008. Besides that, there is a decree of Wonosobo Government point 9 year 2009 about the retribution of health services in Puskesmas of Wonosobo.